2011
DOI: 10.5090/kjtcs.2011.44.2.137
|View full text |Cite
|
Sign up to set email alerts
|

Mid- to Long-term Results of Surgical Treatment of ASD in Patients over 60 Years Old

Abstract: BackgroundThere is controversy about the benefit of surgical correction of an atrial septal defect (ASD) in patients over 60 years old. The purpose of this study was to determine whether surgical treatment is beneficial in those 60 years of age or older.Materials and MethodsWe reviewed the clinical course of 57 patients (mean age: 63.54±5.59 years) diagnosed with an isolated secundum ASD after the age of 60. The 24 patients (group A) who underwent surgical repair were compared with the 33 patients (group B) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In contrast, Jeong et al found much higher mortalities of 21% after closure and 27% with no closure with a mean follow-up of 6.8 years. 24 John Sutton et al 4 found that adult patients with ASD closure did not have altered survival compared with a matched control group 5–10 years after closure. The very low long-term survival of 40% in patients with closure found by Murphy et al 1 was not replicated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Jeong et al found much higher mortalities of 21% after closure and 27% with no closure with a mean follow-up of 6.8 years. 24 John Sutton et al 4 found that adult patients with ASD closure did not have altered survival compared with a matched control group 5–10 years after closure. The very low long-term survival of 40% in patients with closure found by Murphy et al 1 was not replicated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Kutty et al 16 showed a mortality rate of 3% at the end of follow-up ranged from 5 to 20years. Jeong et al 17 found a much higher mortalities of 21% after closure and 27% mortality in patients with no closure, with a mean follow-up of 6.8years. John Sutton et al 18 revealed that adult patients with ASD closure did not have altered survival compared with a matched control group 5 to 10years after closing.…”
Section: Discussionmentioning
confidence: 98%